2018
DOI: 10.1002/ange.201805868
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Peptidyl Virus‐Like Particles Enable Targeted Delivery of Genetic Cargo

Abstract: We report as trategy to construct peptidyl virus-like particles (pVLPs) by mimicking the human immunodeficiency virus and simian virus 40. We designed two viral peptides with cell/nucleus-targeting capabilities that can co-assemble in their active conformations into well-defined nanoparticles.The selfassembled nanoparticles can encapsulate the DNAofclustered regularly interspaced short palindromic repeat associated proteins 9( CRISPR/Cas9) to form biodegradable pVLPs with excellent cell-targeting ability and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Another work from the same group demonstrated that the formed nanoribbons achieved high gene-transfection efficacy in HEK293 cells 51. Although the detailed mechanism of this observation remain to be elucidated, this work may lead to a facile approach to fabricate viral-mimetic nanostructure 52 with certain stability in vitro .…”
Section: Virus-like Peptide Nanostructures For Gene Deliverymentioning
confidence: 82%
“…Another work from the same group demonstrated that the formed nanoribbons achieved high gene-transfection efficacy in HEK293 cells 51. Although the detailed mechanism of this observation remain to be elucidated, this work may lead to a facile approach to fabricate viral-mimetic nanostructure 52 with certain stability in vitro .…”
Section: Virus-like Peptide Nanostructures For Gene Deliverymentioning
confidence: 82%
“…These NPs possess a strong potential to deliver the CRISPR/Cas9 system within specific cells [98]. Out of these NPs, black phosphorus NPs, calcium carbonate NPs, and notably AuNPs have attracted the attention to develop more advanced carrier structures (Table 2) [11, 12, 53, 99–124].…”
Section: Delivery Strategies Of the Crispr/cas9 Complex Within Cancer...mentioning
confidence: 99%
“…In recent years, peptide-based materials have received increasing attention in the biomedical field because of their structural versatility and good biocompatibility. [114][115][116] Functionalizable peptide materials can be the basis for constructing artificial enzymes. Fry et al prepared an artificial peroxidase with tunable catalytic activity by modulating the peptide sequence and the structure of the peptide-based assemblies.…”
Section: Peptide-based Materials@mipsmentioning
confidence: 99%